Implementation of Lean in SME, Experiences From a Swedish National Program - Medbo, Lars; Carlsson, Dan (International Journal of Industrial Engineering and Management, 2013)
This paper presents experiences from implementation of Lean in small and medium sized enterprises (SME). In Sweden, a national program, “The Production Leap”, to support and strengthen the production capabilities of small and medium-sized enterprises by implementing Lean production has been proceeding since 2007. The program consists of three main parts: regional seminars for inspiration, courses for education in Lean, and coaching of individual companies. Until June 2012 more than 1000 employees have participated in courses and more than 130 companies in coaching. Research institutes, regional industrial development associations, universities, unions, employers’ organisations and companies have co-operated in the development and operation of the program. The program has been evaluated as very successful. The aim of this paper is to describe the program and how the methodology to develop companies has evolved. Experiences from the authors’ participation in the program from the start as well as evaluations of the program and of participating companies are used in the analysis. Emphasis is on factors leading to successful development and transformation of companies. Based on questions such as: what activities, who to involve, what is progress, what in the context is important, what is generic, how to reach sustainable transformation? Examples from companies participating in the program will be presented and discussed. Article history: Received (11.09.2012); Revised (20.02.2013); Accepted (28.06.2013)